INDIAN PREMIER LEAGUE: A NEW SPORTS ECONOMICS MODEL - Agarwal, Mukesh; Goel, Preeti; Goel, Anek (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The IPL has advanced beyond other sports organizations by using economists to optimize its revenue generation strategies. The marketing initiatives are appealing and executed systematically, providing advertising and sponsors enhanced marketing chances. The presence of multiple franchisees as competitors fosters a substantial fan base for the organization. The foundation would thereafter augment the income derived from television revenues, benefiting both the franchisee and the organization. The fan base is distributed over many geographical regions, and the sport is played in multiple locales. This indicates that spectators incur different expenses to view the sport. This strategy could assist small businesses in promoting and locally advertising their products, such as suiting, shirting’s, designer sunglasses, and shaving creams, as these nascent players are more accessible and financially feasible for burgeoning middle-class enterprises. Fans purchase items including apparel, souvenirs, autographed mementos, and cricket equipment. IPL Seasons 3 and 4 both received the highest engagement from the 35+ age demographic, but IPL Season 4 experienced a rise in viewership among children. Fifty-seven businesses gained visibility via sixteen accessories platforms, contributing 2% to the overall 'In-stadia' advertising share. The entity IPL was established in 2008 and subsequently undertook a vigorous marketing campaign to promote its business; nevertheless, its most significant achievement was the live telecast of IPL matches on YouTube, which attracted millions of users.